The Adaptive Analysis of Shock Signals on the Basis of Improved Morlet Wavelet Clusters - Haikun Yang; Hong-Xia Pan (Shock and Vibration)
Morlet wavelets do not satisfy the permissibility condition of wavelet analysis, and there are therefore no inverse transformations for Morlet wavelet transforms. In this paper, we put forward the Yang and Pan transform (YPT), which is an adaptive discrete analysis method for shock signals. First, we improved the Morlet wavelet so that the centre and radius of the frequency window can be easily adjusted in the frequency domain. Second, we proposed the extremum frequency concept and analysed the extremum situation of the improved Morlet wavelet. Third, combining the improved Morlet wavelet and extremum frequency, we advanced the theory of the YPT, which does not need to satisfy the permissibility condition. We then continued by using a smoothing operator that can smooth the potentially distorted signal reconstructed after being analysed by the YPT and filtered by using the threshold filtering theory. This operator proved to be simple and efficient. Finally, a noisy signal was reconstructed after being analysed and filtered using the YPT and threshold filtering, respectively, to verify the validity of the theory, and the YPT was compared with the discrete wavelet transform (DWT). As a supplement to the theory in engineering, the shock signals about a gun automatic mechanism were also analysed using the theory in this paper. Good results were obtained, thereby demonstrating that the YPT can be helpful to further extract the features of shock signals in pattern recognition and fault diagnosis.